Copyright Protection Regarding Plagiarism Cases and Warkopi Ethics Against Warkop DKI (Universitas Negeri Semarang, 2020)
The existence of technological advances provides opportunities for the development of technological applications. The use of technology that is not based on knowledge of the rule of law can lead to violations, and does not rule out the possibility of violations to the detriment of the creator. With the internet network will increase the number of violations because it can be seen by the wider community. Copyright is regulated in Law Number 28 of 2014 (Copyright Law) concerning Copyright. The law explains that copyright is part of the intellectual property rights of protected objects. In fact, even though the Indonesian people have used the new copyright law (UUHC), there are still many copyright violations. Like what Warkopi did to Warkop DKI, Warkopi imitated the clothes and characters of Dono, Kasino, and Indro without permission, all three of whom were considered to have committed plagiarism as well as copyright infringement. Therefore, the state must provide legal protection as a form of appreciation for the creation.